Oxytocin at elective caesarean delivery: a dose‐finding study in women with obesity. (23rd November 2020) - Peska, E.; Balki, M.; Maxwell, C.; Ye, X. Y.; Downey, K.; Carvalho, J. C. A.
Summary: Prophylactic oxytocin administration at the third stage of labour reduces blood loss and the need for additional uterotonic drugs. Obesity is known to be associated with an increased risk of uterine atony and postpartum haemorrhage. It is unknown whether women with obesity require higher doses of oxytocin in order to achieve adequate uterine tone after delivery. The purpose of this study was to establish the bolus dose of oxytocin required to initiate effective uterine contraction in 90% of women with obesity (the ED90 ) at elective caesarean delivery. We conducted a double‐blind dose‐finding study using the biased coin up‐down design method. Term pregnant women with a BMI ≥ 40 kg.m −2 undergoing elective caesarean delivery under regional anaesthesia were included. Those with conditions predisposing to postpartum haemorrhage were not included. Oxytocin was administered as an intravenous bolus over 1 minute upon delivery of the fetus. With the first woman receiving 0.5 IU, oxytocin doses were administered according to a sequential allocation scheme. The primary outcome measure was satisfactory uterine tone, as assessed by the operating obstetrician 2 minutes after administration of the oxytocin bolus. Secondary outcomes included the need for rescue uterotonic drugs, adverse effects and estimated blood loss. We studied 30 women with a mean (SD) BMI of 52.3 (7.6) kg.m ‐2 . The ED90 for oxytocin was 0.75 IU (95%CI 0.5–0.93 IU) by isotonic regression and 0.78 IU (95%CI 0.68–0.88 IU) by the Dixon and Mood method. Our results suggest that women with a BMI ≥ 40 kg.m ‐2 require approximately twice as much oxytocin as those with a BMI < 40 kg.m ‐2, in whom an ED90 of 0.35 IU (95%CI 0.15–0.52 IU) has previously been demonstrated.